Massive hemoptysis causing mortality in a post COVID-19 infected Asian male patient: Presenting as pulmonary mucormycosis, pulmonary tuberculosis and later sino-nasal mucormycosis. (2021) - Rana, Gunjan; Gautam, Sachin; Mawari, Govind; Daga, Mradul Kumar; Kumar, Naresh; Raghu, RV
Abstract: While the developed nations are discussing giving a third dose of the COVID-19 vaccine to immunocompromised individuals, there are still challenges that are of global concern, especially in developing countries. The Delta variant which is predominantly responsible for the disease burden has now been reported in over 148 countries. The catastrophe caused in the Indian subcontinent has highlighted some associations, most notable being the unprecedented rise in the cases of mucormycosis in COVID-19 patients referred to as CAM (COVID-19 associated mucormycosis). This life-threatening opportunistic fungal infection which was historically associated with immunosuppression has reached a new peak as its incidence has increased many folds with the advent of COVID-19. Here we present one of the very first Case reports on how to post COVID immunosuppression state, uncontrolled blood sugar levels in the background of diabetic ketoacidosis led to the development of pulmonary mucormycosis with superimposed pulmonary tuberculosis and later Sino-nasal mucormycosis eventually leading to life-threatening massive hemoptysis, causing mortality of a post-COVID-19 infected middle-aged diabetic Asian male patient who presented twenty days after COVID-19 infection. However, our patient did not have risk factors such as severe COVID-19 infection requiring hospitalization, use of steroids or other immunomodulatory drugs like remdesivir or tocilizumab. Our case report aims to bring forth this post COVID pulmonary mucormycosis with pulmonary tuberculosis association as well as highlight the fact that tuberculosis is still a major public health burden that should not be forgotten in the fight to combat the pandemic.